KIPRAH KH. ZAINAL ABIDIN DALAM DAKWAH DI SIDOARJO TAHUN 1783-1848 M - Syafira Qolila Nurjanah; Anis Bahtiyar (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2022)
Abstract: This article was written to find out the biography of KH. Zainal Abidin. This article focuses on three questions, namely: (1) What is the brief biography of KH. Zainal Abidin?, (2) What are the social and cultural conditions that shape KH. Zainal Abidin?, (3) How did KH. Zainal Abidin in preaching in Sidoarjo Year 1783-1848 M?. This study uses a sociological approach and analysis of role theory by S. Nasution which states that a role is a consequence of a person's status so that status can be seen how one works. In the data collection process, this study refers to the stages of the historical method, namely heuristics, verification, interpretation and historiography. The results of the analysis process can be concluded that: 1) KH. Zainal Abidin was born in 1743 M or 1164 H in Tambak Sumur Sidoarjo, he came from a family that really understood the teachings of Islam so that he grew up to be a tough, pious and religious person. 2) KH. Zainal Abidin was equipped with knowledge, religion and kanuragan because his parents understood that the Tambak Sumur community still strongly adheres to Javanese beliefs. 3) Gait KH. Zainal Abidin, among others, was a pioneering figure at the Sono Islamic Boarding School, played a major role in the Islamization of the Tambak Sumur community and was a reliable writer. Keywords: dakwah, islamisasi, kiprah, KH. Zainal Abidin, Sidoarjo